AB0153 Reduced Regenerative Potential of Salivary Gland Stem Cells in Primary Sjögren's Syndrome. (15th July 2016) - Pringle, S.; Bootsma, H.; Verstappen, G.M.; Vissink, A.; Spijkervet, F.K.L.; Coppes, R.P.; Kroese, F.G.M.
Abstract : Background: The involvement of the epithelium in the pathology of primary Sjögren's syndrome (pSS) has long been proposed. Epithelial cells have potential to transmit immune initiation signals and to serve as autoimmune targets, in addition to their function as saliva channeling/modulating agents in the salivary gland. Recently, we have demonstrated isolation of stem cells from the human salivary gland [1–2]. Salivary gland stem cells (SGSCs) are cultured as clusters of cells, termed salispheres. SGSCs, like all stem cells, possess the ability to self-renew (reproduce themselves) and to differentiate into all salivary gland lineages. Our ability to isolate and characterize the epithelium-derived SGSCs provides a tool to study the involvement of epithelial cells in pSS pathology. Objectives: We aim to isolate SGSCs from biopsies of pSS parotid salivary glands, and characterize their regenerative potential in comparison to healthy controls. This will be a first step towards to assessment of complicity of SGSC/epithelial malfunction in pSS, and in identifying any innate properties specific to pSS-SGSCs. Methods: Salivary gland stem cells were isolated using enzymatic and mechanical digestion, in a protocol adapted from Pringle et al, 2016. The self-renewal capability of pSS-SGSCs was assessed using our published self-renewal assay. The potential immunomodulatory nature of pSS-SGSCs was assessed using qPCR for expression of matrix metalloprotease (MMP) enzymes, and mass spectrometry for identification of immune-related proteins in the medium. Results: Yield of SGSCs from pSS biopsies was markedly lower than from healthy control tissues (Figure 1 A-C). When exposed to a self-renewal assay, SGSCs from pSS biopsies generated significantly fewer SGSCs (Figure 1 D-F). Expression of MMP2 and MMP9 was notably higher in SGSCs isolated from pSS biopsies. In addition, proteins involved in both pro-inflammatory (polymeric immunoglobulin receptor, immunoglobulin kappa constant) and anti-inflammatory (annexin A1) immunereactions and in rheumatoid arthritis (rheumatoid arthritis antigen A-47) were detected in conditioned medium from pSS SGSCs at greater levels than controls. These data suggest the transcriptome and secretome of SGSCs from pSS biopsies differs significantly from that of healthy controls. Conclusions: Our preliminary data demonstrates that the established SGSC isolation technique can be applied to the study of primary Sjögren's Syndrome. Furthermore our data suggest there is an an innate difference in the regenerative potential and immune-reactive nature of SGSCs from pSS biopsies, compared to healthy controls. We anticipate that full characterization of SGSC from pSS biopsies will at least shed light on the mechanisms underpinning epithelial cell involvement in pSS, and permit development of new therapeutic and/or biological agents for the treatment of primary Sjögren's' Syndrome. References: Pringle, S. et al. Human salivary gland stem cells functionally restore radiation damaged salivary glands (2016). Stem Cells (in press). Lombaert, I. M. A. et al.Rescue of Salivary Gland Function after Stem Cell Transplantation in Irradiated Glands (2008). PLoS One 3(4): e2063. Disclosure of Interest: None declared